A Survey on Sentiment Analysis And Summarization For Prediction (International Journal of Engineering and Computer Science, 2014)
Social Networking portals are been widely used by people all over the world, they use it for expressing their views (sentiment) on different issues like products, movie review and also for expressing their opinion on different political parties. These opinion or sentiment can be used for predicting or analyzing the view of people on services which could be beneficial for various companies and political parties to understand their customer and take needful steps for improvising their efficiency. Summarization of tweets will allow understanding hidden events and sentiment with respect to events. In this paper, we firstly discuss the realms which can be predicted with current social media Secondly, we will see how summarization of sentiment with respect to events will allow people of interest to take decision easily.